2014
DOI: 10.1186/1471-2121-15-15
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular trafficking and endocytosis of CXCR4 in fetal mesenchymal stem/stromal cells

Abstract: BackgroundFetal mesenchymal stem/stromal cells (MSC) represent a developmentally-advantageous cell type with translational potential.To enhance adult MSC migration, studies have focussed on the role of the chemokine receptor CXCR4 and its ligand SDF-1 (CXCL12), but more recent work implicates an intricate system of CXCR4 receptor dimerization, intracellular localization, multiple ligands, splice variants and nuclear accumulation. We investigated the intracellular localization of CXCR4 in fetal bone marrow-deri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 62 publications
3
39
0
Order By: Relevance
“…However, several groups have reported that CXCR4 expression decreases rapidly after MSCs isolation and only a very small percentage of cells or none at all express CXCR4 after a few passages [31, 32]. In fact, in vitro expansion of MSCs induces progressive internalization of CXCR4 as a way for cells to adapt to culture conditions, to the point where there is no CXCR4 remaining on their surface [12, 3335]. Considering that ADHLSCs emerge from the parenchymal fraction of the adult liver after about one month in culture and then need several more weeks to reach passages 4 to 6 at which time they are traditionally used for experiments, we suspected that the same phenomenon may be taking place.…”
Section: Resultsmentioning
confidence: 99%
“…However, several groups have reported that CXCR4 expression decreases rapidly after MSCs isolation and only a very small percentage of cells or none at all express CXCR4 after a few passages [31, 32]. In fact, in vitro expansion of MSCs induces progressive internalization of CXCR4 as a way for cells to adapt to culture conditions, to the point where there is no CXCR4 remaining on their surface [12, 3335]. Considering that ADHLSCs emerge from the parenchymal fraction of the adult liver after about one month in culture and then need several more weeks to reach passages 4 to 6 at which time they are traditionally used for experiments, we suspected that the same phenomenon may be taking place.…”
Section: Resultsmentioning
confidence: 99%
“…2B). However, of note, constitutive trafficking is not a unique feature of scavenger ACKRs, as increasing, emerging evidence indicates that several conventional chemokine receptors also undergo constitutive internalization and recycling in specific cell types and conditions (CXCR4 [141][142][143]; CXCR3 [144]; CCR7 [145]; CCR1 [146]). Interestingly, constitutive trafficking correlates with ACKR subcellular localization, as scavenger ACKRs are mainly located in recycling endosomes [138][139][140] [unpublished results], whereas transporter and presenter ACKRs are preferentially expressed on the cell membrane [42, 62,82,128,129] (Fig.…”
Section: Trafficking Properties Of Ackrsmentioning
confidence: 99%
“…Rapid degradation of E-cadherin, aberrant trafficking, and recycling of integrins are a few of the underlying mechanisms through which endocytosis promotes oncogenesis and metastasis. Recent evidence indicates that altered endocytosis in cancer cells also promotes aberrant tyrosine kinase and G-protein-coupled receptor signaling, either by recycling them at a faster rate through the cell surface or enabling altered receptor signaling from the endosomal compartment (27,28,46). Thus, it is important to understand the mechanisms by which the NRP2 axis regulates endocytosis in cancer cells and the effect that the NRP2 axis has on regulating endocytic trafficking of other tyrosine kinase and G-protein-coupled receptors, thereby modifying their functions.…”
Section: Discussionmentioning
confidence: 99%